Pengaruh Kegiatan Senam Terhadap Kecerdasan Kinestetik Anak Kelompok A di TK PERTIWI II Metuk Mojosongo Boyolali Tahun Ajaran 2015/ 2016 - Prihantini, Ratna; , Drs. Haryono Yuwono, M.Pd (2016)
The aim of this study was to determine the effect of gymnastic activities on children's kinesthetic intelligence in group A. Kindergarten Pertiwi II Metuk. This study was an experimental study. The experimental design used is an a preexperimental design types one group pretest- posttest design. The subjects in this study were children in group A amounting to 20 children. The data collection technique used is observation. The data were analyzed using t-test. The result of children's kinesthetic intelligence in group A obtained an average score of 11,55 on the pretest and an average score of 14 on the posttest. The results of t-test data analysis obtained that t count -11.052 ≤ t 1. 729. This shows that Ha is accepted an Ho is rejected. The conclusion of this study is that gymnastic activities effect on children's kinesthetic intelligence in group A Kindergarten Pertiwi II Metuk